An Examination of the Human Factors in Cybersecurity: Future Direction for Nigerian Banks - Ajufo, George; Qutieshat, Abubaker (Indonesian Journal of Information Systems, 2023)
Information and communication technology has become necessary for conducting business operations and ensuring business survival in Nigerian banks. However, this has come with some encumbrances, as this technology is vulnerable to attacks due to technical or human factors. These human factors have been very challenging for organizations due to their multi-dimensional nature and the fact that humans have been responsible for most cybersecurity incidents. Resolving issues arising from cybersecurity incidents is expensive and time-consuming. Therefore, this study is crucial as it will enable Nigerian banks witnessing increased attacks to take preventive measures and reduce the enormous expenditure required for remediation. This study adopts a literature review approach, reviewing previous studies on human factors in cybersecurity to determine the factors responsible for successful cyber-attacks and their suggested mitigations. The findings categorize these human factors into social engineering, poor information security culture, risky password practices, stress, burnout, and security fatigue. The study presents mitigations but notes that training and cybersecurity awareness are the most common reoccurring pre-emptive actions recommended. This research is significant as very little prior research has been conducted in this area targeted at the Nigerian banking sector. Practically, the findings of this study are expected to point Nigerian banks toward the critical human factors that they need to concentrate on to minimize the success rate of cyber-attacks and reduce the associated costs of recovering from these attacks.